Impact of FEC Additive on SEI Structure Formed on a Carbon Negative Electrode Studied by HAXPES. (9th December 2015) - Matsumoto, Masashi; Sanada, Takashi; Takao, Naoki; Mogi, Masato; Matsuda, Tomoyuki; Ando, Keisuke; Imamura, Daichi; Imai, Hideto
Abstract : In order to understand the impact of fluoroethylene carbonate (FEC) additive on the improvement of the battery performance, such as the solid electrolyte interphase (SEI) stability, we investigated the structure, composition and dynamics for formation of the SEI formed on the carbon negative electrodes by using hard X-ray photoelectron spectroscopy (HAX-PES). The organic SEI species such as CH3 CH2 OCO2 -Li (LEC), (CH2 O-CO2 -Li)2 (LEDC), (CH2 O-Li)2 and (CO2 -Li)2 are the main reduction components of the SEI during discharge. The SEI layer continues to grow gradually as the number of the charge and discharge cycling increases. The stable SEI components, LiF and polymerization products, produced from FEC additives suppress the formation of the unstable SEI species such as LEC, LEDC, (CH2 O-Li)2 and (CO2 -Li)2 and the growth of the SEI with the charge and discharge cycle increase. This leads to the improvement of the battery performance such as the capacity retention and the overall impedance.